Evaluation of the resonance enhancement effect in neutrinoless double-electron capture in 152Gd, 164Er, and 180W atoms - Fang, Dong-Liang; Blaum, Klaus (Physical review. C, Nuclear physics, 2012)
We study the resonant neutrinoless double-electron capture (0νECEC) in 152Gd, 164Er, and 180W atoms, associated with the ground-state to ground-state nuclear transitions. The corresponding matrix elements are calculated within the deformed quasiparticle random-phase approximation using the realistic charge-dependent Bonn (CD-Bonn) nucleon-nucleon interaction. The half-lives are estimated with the use of the most recent precision data on the Q values of these processes. Perspectives of experimental search for the 0νECEC with the isotopes 152Gd, 164Er, and 180W are discussed.